'A picture is worth a thousand words'—A photovoice study exploring health professionals' experiences during the COVID‐19 pandemic. Issue 23 (30th May 2021) - Badanta, Bárbara; Acevedo‐Aguilera, Rosa; Lucchetti, Giancarlo; de Diego‐Cordero, Rocío
Abstract: Aim: To elicit the experiences and perspectives of health professionals working on the frontline in the COVID‐19 pandemic. Background: Although some qualitative studies have been carried out in health professionals during COVID‐19 pandemic, to our knowledge, no study has used the Photovoice method. Design: A qualitative descriptive study using Photovoice was carried out between March and June 2020. Methods: A total of 20 health professionals were recruited from public and private healthcare services. The participants were invited to share photographs about their experiences while working during COVID‐19 pandemic. Following the Photovoice method, audio‐recorded interviews were conducted. The data were analysed using the 'SHOWED' mnemonic, with five questions answered about each photograph. The EQUATOR checklist has been used. Results/Findings: Three themes emerged: (1) Personal attitudes of health professionals; (2) Support from the community; and (3) Management of institutional resources. Despite the fact that health professionals in this study were exposed to major risks while caring for patients with COVID‐19' they felt a strong sense of responsibility towards the community. In order to handle these stressful situations, they used coping mechanisms, good humour and leisure, but also received support from the population, who saw them as highly skilled health professionals. Conclusion: These findings highlight the essential role of health professionals in the COVID‐19 pandemic and the tireless work they are carrying out to provided highly skilled care. Relevance to clinical practice: These findings could contribute to raise awareness on the needs of health professionals during the pandemic, allowing managers to plan strategies to ensure the safety, and well‐being of these professionals, as well as adopting similar strategies in their practice to create a space for critical reflection through participatory approaches.